The Yen-Dollar Rate : Have Interventions Mattered? - Ramaswamy, Ramana; Samiei, Hossein (Washington, D.C. : International Monetary Fund, 2000)
Using daily data for 1995-99, this paper estimates a simple forward looking model of the exchange rate to show that foreign exchange interventions have, on the whole, had small but persistent effects on the yen-dollar rate. Contrary to conventional wisdom, sterilized interventions have mattered. Consistent with conventional wisdom, coordinated interventions have a higher probability of success and move the yen-dollar rate by a larger margin than unilateral interventions. A probit model indicates that both an excessive appreciation and depreciation of the yen provoke interventions, and that interventions occur in clusters-if there is one today, there will likely be another tomorrow.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet